Development of a surveillance scheme for equine influenza in the UK and characterisation of viruses isolated in Europe, Dubai and the USA from 2010-2012 - Woodward, Alana L.; Rash, Adam S.; Blinman, Donna; Bowman, Samantha; Chambers, Thomas M.; Daly, Janet M.; Damiani, Armando; Joseph, Sunitha; Lewis, Nicola; McCauley, John W.; Medcalf, Liz; Mumford, Jemny; et al. (Elsevier, 2014)
Equine influenza viruses are a major cause of respiratory disease in horses worldwide and undergo antigenic drift. Several outbreaks of equine influenza occurred worldwide during 2010-2012, including in vaccinated animals, highlighting the importance of surveillance and virus characterisation. Virus isolates were characterised from more than 20 outbreaks over a 3-year period, including strains from the UK, Dubai, Germany and the USA. The haemagglutinin-1 (HA1) sequence of all isolates was determined and compared with OIE-recommended vaccine strains. Viruses from Florida clades 1 and 2 showed continued divergence from each other compared with 2009 isolates. The antigenic inter-relationships among viruses were determined using a haemagglutination-inhibition (HI) assay with ferret antisera and visualised using antigenic cartography. All European isolates belonged to Florida clade 2, all those from the USA belonged to Florida clade 1. Two subpopulations of clade 2 viruses were isolated, with either substitution A144V or I179V. Isolates from Dubai, obtained from horses shipped from Uruguay, belonged to Florida clade 1 and were similar to viruses isolated in the USA the previous year. The neuraminidase (NA) sequence of representative strains from 2007 and 2009 to 2012 was also determined and compared with that of earlier isolates dating back to 1963. Multiple changes were observed at the amino acid level and clear distinctions could be made between viruses belonging to Florida clade 1 and clade 2.